2020
DOI: 10.3390/genes11040441
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue: Genetics of Biodegradation and Bioremediation

Abstract: Many different biodegradation pathways, both aerobic and anaerobic, have already been characterised, and the phylogenetic relationships among catabolic genes within the different types of pathways have been studied. However, new biodegradation activities and their coding genes are continuously being reported, including those involved in the catabolism of emerging contaminants or those generally regarded as non-biodegradable. Gene regulation is also an important issue for the efficient biodegradation of contami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Genomic studies have demonstrated that bacteria belonging to the genera Alcaligenes, Burkholderia, Mycobacteria, Rhodococcus and Pseudomonas [92] are capable of degrading organic contaminants such as aliphatic and aromatic compounds and converting them into either carbon dioxide, water, or biomass, which is essential for their growth [93]. In addition, synthetic chemicals used in pesticides, dyes, solvents, and refrigerators are often persistent in nature and hence are considered hazardous to the environment and humans, as they are toxic and insoluble and are often accumulated in high concentrations [94,95]. The biotransformation of these organic compounds can be further exploited for the treatment of contaminated water and soils through DNA recombinant techniques by constructing strains with an enhanced ability to degrade several toxic compounds.…”
Section: Genes Involved In Biodegradationmentioning
confidence: 99%
“…Genomic studies have demonstrated that bacteria belonging to the genera Alcaligenes, Burkholderia, Mycobacteria, Rhodococcus and Pseudomonas [92] are capable of degrading organic contaminants such as aliphatic and aromatic compounds and converting them into either carbon dioxide, water, or biomass, which is essential for their growth [93]. In addition, synthetic chemicals used in pesticides, dyes, solvents, and refrigerators are often persistent in nature and hence are considered hazardous to the environment and humans, as they are toxic and insoluble and are often accumulated in high concentrations [94,95]. The biotransformation of these organic compounds can be further exploited for the treatment of contaminated water and soils through DNA recombinant techniques by constructing strains with an enhanced ability to degrade several toxic compounds.…”
Section: Genes Involved In Biodegradationmentioning
confidence: 99%
“…Another area for potentially applying metagenomics is in the characterization of genes involved in biodegradation, as it is thought that 30-50% of those genes remain uncharacterized. Identifying these genes is particularly important as they may be involved in degrading a broader range of substrates, a smaller subset of substrates or perform an entirely new function (Igeno et al, 2019;Joye & Kostka, 2020;Salvador et al, 2020;Santero & Diaz, 2020).…”
Section: Focus On Specific Omics and Their Application In Bioremediation Imentioning
confidence: 99%
“…Summarily, microbiologists were able to apply the OMICs tools and directly study the intricacies of microbial interrelationships in their habitats, from both oil-contaminated and uncontaminated water and sediment samples. These enable scientists to know the microbial reactions to hydrocarbon contamination and the methodological underpinnings of microbesassisted environmental reclamation, in unparalleled detail (Chikere, 2013;Rathoure & Dhatwalia, 2016;Kaster & Sobol, 2020;Kumari & Kumar, 2020;Santero & Diaz, 2020). Problems/Challenges of OMICs Approaches Despite the numerous benefits and prospects of the application of the OMICs in microbial bioremediation, there are still certain challenges needing to be addressed before the OMICs can reach their full potential, especially in developing countries.…”
Section: Hatzenpichler Et Al (2016)mentioning
confidence: 99%